Technical queries of a 3D design custom-made implant made from titanium particles for maxillofacial bone reconstruction. (17th August 2020) - Armencea, G.; Cosma, C.; Dinu, C.; Onisor, F.; Lazar, M.; Berce, P.; Balc, N.; Baciut, M.; Bran, S.
Abstract: Accurate 3D bone reconstruction is one of the most difficult tasks to achieve in maxillo-facial surgery. In the present study, a zygomatic bone defect was reconstructed with a custom made implant fabricated by selective laser melting (SLM) processing from titanium particles. 2 years follow-up revealed diplopia (double vision) resolution, as well as esthetic and functional stabile reconstruction. Technical queries regarding the fabrication process and medical reconstruction are discussed.